Legal Protection For Consumers In Purchasing Homes From Default Actions Of The Developer - Dian HADIATI; Sihabudin SIHABUDIN; Hanif NURWIDHIYANTI (Indonesia Strategic Sustainability, 2022)
Hundreds of victims of the alleged Quranic Residence housing fraud, in Kemang, Bogor Regency, demanded their money be returned immediately. The losses suffered by the victims reached 12 billion. The claim was submitted after they felt cheated by PT Alfatih Bangun Indonesia, as a housing developer under the guise of sharia. PT Alfatih Bangun Indonesia has defaulted on consumers and shirked its responsibilities. The house promised by the developer until now has not been built and is still in the form of vacant land. In accordance with the legislation on consumer protection, PT Alfatih Bangun Indonesia as a developer must compensate and even get criminal for his treatment. The purpose of this writing is to find out and analyze the legal protection of consumers for wanprestasi carried out by developers